Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nu12010170
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Weight Change One Year after Delivery Are Associated with Cardiometabolic Risk Factors at Six Years Postpartum in Mexican Women

Abstract: Pregnancy is a contributor to the obesity epidemic in women, probably through postpartum weight retention (PPWR), weight gain (PPWG), or a combination of both (PPWR + WG). The contribution of these patterns of postpartum weight change to long-term maternal health remains understudied. In a secondary analysis of 361 women from the prospective cohort PROGRESS, we evaluated the associations between patterns of weight change one year after delivery and cardiometabolic risk factors at six years postpartum. Using pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Ideally, this should include an interdisciplinary approach to address weight management, an important part of CVD risk management. Studies show that postpartum weight retention and changes impact cardiometabolic risk in diverse populations [18,19]. Common themes that emerged from prior studies were a need for cost-effective longitudinal intervention, identifying barriers to healthcare attendance, and developing proactive strategies to promote participation [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, this should include an interdisciplinary approach to address weight management, an important part of CVD risk management. Studies show that postpartum weight retention and changes impact cardiometabolic risk in diverse populations [18,19]. Common themes that emerged from prior studies were a need for cost-effective longitudinal intervention, identifying barriers to healthcare attendance, and developing proactive strategies to promote participation [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Excess postpartum weight retention has been linked to long-term maternal-infant outcomes, including metabolism changes in mothers, difficulties in breastfeeding initiation, and infant's microbiome [8]. Women who did not return to their pre-pregnancy weight and gained weight through one-year postpartum are at increased risk of obesity, insulin resistance, and metabolic syndrome at six-year postpartum [9]. Common risk factors of postpartum weight retention are related to pre-pregnancy and pregnancy periods, including pre-pregnancy BMI, gestational weight gain, and parity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found that women with PPWR, PPWG and PPWR þ WG, compared with those who returned to their pregestational weight by 1 year postpartum, had increased adiposity 6 years after delivery. We also found that PPWR þ WG was associated with metabolic alterations such as insulin resistance (13) . In the current study, we extend these results by identifying the contribution of specific modifiable factors to the risk of each of the patterns of weight change.…”
Section: Discussionmentioning
confidence: 52%
“…retention of gestational weight, followed by postpartum weight gain) (6,11,12) . We recently showed that PPWR, PPWG and PPWR þ WG were associated with increased adiposity at 6 years postpartum (13) . PPWR þ WG was the only pattern directly associated with metabolic markers, such as insulin resistance (13) .…”
mentioning
confidence: 96%
See 1 more Smart Citation